PENGARUH PERHATIAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP DISIPLIN BELAJAR KELAS X AKUNTANSI LEMBAGA KEUANGAN (AKL) SMK NEGERI 1 PEMATANG SIANTAR - Yohannes Tampubolon; Anton Luvi Siahaan; Paulina Herlina Sirait (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to obtain knowledge regarding the influence of parental attention and learning motivation on the learning discipline of students in class x Financial Accounting at SMK Negeri 1 Pematangsiantar.This research is quantitative in type. The sampling technique used a probability sampling technique of 108 respondents. Data collection techniques use questionnaires. Instrument testing uses normality tests and reliability tests. The data analysis technique uses classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test and hypothesis testing, namely multiple linear regression analysis, t-test, f-test and coefficient of determination.The results of this study state that: 1) Parental attention has a significant and influential effect on student learning discipline. This result can be seen in the t test where the t value of parental support (7.064) > t table value (1.65936). The significant value obtained by parental support was 0.000 <0.05. 2) learning motivation has a significant and influential effect on student learning outcomes. This result can be seen in the t test where the tcount value of learning motivation (3.441) > ttable value (1.65936). The significant value obtained is 0.001 <0.05, which means the variable is significant. 3) Parental attention and learning motivation together have a significant influence on student learning outcomes. This result can be seen in the F test where the Fcount value (38.006) > Ftable value (2.69). The R Square coefficient of determination test is known to be 0.420, which means that 42% of the variables of parental support and learning motivation influence learning outcomes and 58% are the influence of other variables not examined in this research.